1992
DOI: 10.1128/iai.60.9.3852-3860.1992
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bactericidal activity of anticapsular antibody by nonspecific antibodies reactive with surface-exposed antigenic determinants on Actinobacillus pleuropneumoniae

Abstract: In an attempt to understand the mechanism of serum resistance in ActinobaciUus pleuropneumoniae, in the present study we examined various interactions among the bacterial surface constituents, serum antibodies, and complement. Analysis of swine sera revealed the presence of anticapsular antibodies in convalescent-phase sera but not in preimmune sera. Both types of sera contained antibodies which reacted with each of 14 polypeptides present in saline extracts of the bacteria. Absorption of the preimmune sera wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
1
0
2
Order By: Relevance
“…Analysis of the resistance, using sublethal polymyxin B to permeate the outer membrane and sensitize the bacteria, showed that A. pleuropneumoniae was serum-resistant through a quite different mechanism from that seen in strains of E. coli (Rycroft & Cullen, 1990b). Further investigations showed that the mechanism of resistance involved interference by blocking antibody to lipopolysaccharide and other antigens (Udeze & Kadis, 1992b;Ward & Inzana, 1994).…”
Section: Structure and Distribution Of Apx Toxin Genesmentioning
confidence: 99%
“…Analysis of the resistance, using sublethal polymyxin B to permeate the outer membrane and sensitize the bacteria, showed that A. pleuropneumoniae was serum-resistant through a quite different mechanism from that seen in strains of E. coli (Rycroft & Cullen, 1990b). Further investigations showed that the mechanism of resistance involved interference by blocking antibody to lipopolysaccharide and other antigens (Udeze & Kadis, 1992b;Ward & Inzana, 1994).…”
Section: Structure and Distribution Of Apx Toxin Genesmentioning
confidence: 99%
“…Tras la inoculación en ratones y cerdos, el LPS induce una neumonía intersticial, multifocal o consolidada, con infiltración de células inflamatorias, en la que la gravedad de las lesiones se relaciona con la dosis utilizada. Sin embargo, este factor endotóxico es incapaz de reproducir por sí solo el cuadro de lesión característico de la pleuroneumonía, ya que no origina hemorragias y la necrosis está menos difundida (Udeze et al, 1987;Jewen, 1994). Tampoco se consigue una protección adecuada frente a la enfermedad mediante la inmunización con LPS puro Inzana et al, 1988).…”
Section: Lipopolisacárido (Lps)unclassified
“…el modelo murino se ha utilizado frecuentemente como una alternativa experimental de primer nivel, en particular en los estudios de inmunidad y virulencia de A. pleuropneumoniae. La mayoría de los investigadores ha concluido, sin embargo que la susceptibilidad de este animal a la infección por A. pleuropneumoniae depende de la cepa o línea de ratón utilizadas y que este animal representa un modelo adecuado para el estudio de la fase aguda de la enfermedad, aunque no para la evaluación del proceso en su conjunto(Sebunya y Sanders, 1982, Fenwik et al, 1986Udeze et al, 1987; Inzana et al, 1988; Gomal, y…”
unclassified